Effect of a sublethal high‐pressure homogenization treatment on the fatty acid membrane composition of probiotic lactobacilli. (15th October 2013) - Tabanelli, G.; Patrignani, F.; Gardini, F.; Vinderola, G.; Reinheimer, J.; Grazia, L.; Lanciotti, R.
Abstract High‐pressure homogenization (HPH) has been proposed to be applied directly to lactic acid bacterial cells at sublethal levels to enhance some functional properties. As the principal target of HPH are the cell surface envelope structures, the aim of this work was to study the effect of a HPH treatment, applied at 50 MPa, on cell membrane stress responses of already‐known functional strains, isolated from Argentinean products. Specifically, the membrane fatty acid composition of cells before and after the sublethal treatment was investigated, and the results showed that plasma membranes, their level of unsaturation and their composition are involved in response mechanisms adopted by microbial cells when subjected to a sublethal HPH stress. In fact, the data obtained demonstrated that the treatment was able to modify the fatty acid profile of the different strains, although a uniform response was not observed. Further studies are necessary both to elucidate the role of each fatty acid in the cell response mechanisms and to clarify the changes in membrane compositions induced by HPH treatment also in relation to the applicative potential of this technique. Significance and Impact of the Study This study contributed to understand the response mechanisms activated in cells exposed to pressure stress. It has been demonstrated that high‐pressure homogenization (HPH) treatments, conducted at sublethal levels, could increase some important functional and technological characteristics of nonintestinal probiotic strains. The findings of this paper can contribute to elucidate the mechanisms through which these treatments can modify these strain probiotic properties that are related to outermost cell structures, also principal target of HPH.